A Study of the Present Scenario of Early Childhood Education in Bhubaneswar - G.N. Prakash Srivastava; Ranjeata Singh (JOURNAL OF INDIAN EDUCATION, 2025)
The various policies and programmes of education place emphasis on Early Childhood Education (ECE). In this regard, NCERT has also come out with a ‘Minimum Specifications for Pre-schools’ to ensure that every school is equipped with the necessary requirements to cater to early childhood education. The present study covers ten ECE centres in Bhubaneshwar in its study to see if they meet these specifications of NCERT. The finding is hardly encouraging with most of the centres wanting in various aspects of the NCERT norms. There is an urgent need for the quantitative as well as qualitative improvement of these centres.